Serbia and Montenegro : Public Expenditure and Institutional Review, Volume 3. Montenegro - World Bank (Washington, DC, 2013)
This Public Expenditure and Institutional Review (PEIR) aims to help the government of the Federal Republic of Yugoslavia (FRY) in taking their public expenditure reforms further. It analyzes public expenditure practices, and institutions of the two Republics - Serbia and Montenegro - and of the Federal Government, and, evaluates their decision-making, and implementation processes. The cross-cutting topics of the PEIR are: sustainability of public expenditures; strategic allocation of public spending, to maximize growth and welfare within fiscally sustainable limits; and, accountability of the public expenditure system, needed to maintain domestic, and international support for the reconstruction programs of the two Republics. The success of reforms depends on difficult strategic choices: 1) the inherited, distorted fiscal systems, and inefficient budget management practices, call for a realistic focus in selecting the goals of reform; 2) the best solution choice must be derived from the existing structures, and practices; and, 3) the Governments of Serbia and Montenegro should focus on deepening the reforms already initiated, rather than launching a number of new ones. The first volume provides an overview of the public expenditure reform agenda; volume two focuses on the Republic of Serbia and the Federal Government, while volume three discusses public expenditure management issues in Montenegro. The public expenditure problems of the Federal level receive a somewhat limited treatment, as the contours of the future union government takes shape. Similarly, challenges of fiscal decentralization below the Republic level, receive only a brief treatment, actually only in the Serbia volume.